Eliminating the floating-body effects in a novel CMOS-compatible thin-SOI LDMOS - 蒋永恒 罗小蓉 李燕妃 王沛 范叶 周坤 王琦 胡夏融 张波 (Journal of semiconductors, 2013)
A novel CMOS-compatible thin film SOI LDMOS with a novel body contact structure is proposed. It has a Si window and a P-body extended to the substrate through the Si window, thus, the P-body touches the P＋ region to form the body contact. Compared with the conventional floating body SOI LDMOS （FB SOI LDMOS） structure, the new structure increases the off-state BV by 54%, decreases the specific on resistance by 20%, improves the output characteristics significantly, and suppresses the self-heating effect. Furthermore, the advantages of the low leakage current and low output capacitance of SOI devices do not degrade.